The Understanding, Perception And Receptiveness Of Globalisation Amongst Rural East Malaysians - Puyok, Arnold (2004)
Globalisation has become an emerging concern to many parties. It is a catchphrase in the international arena and a rather new phenomenon to local communities. To date, only the urban people have the tenacity and capability in confronting globalisation because they have been exposed to the process almost everyday. For the rural people, globalisation seems to be a new phenomenon. Globalisation is believed to benefit Malaysia in terms of economic development and political stability. This is evident through the massive flow of Foreign Direct Investments (FDls) and diplomatic ties Malaysia has established with other countries. However, globalisation is also believed to have caused irreparable consequences to certain countries embracing it; and this is equated with the serious damage the process has caused to local cultures and traditional values. The rural people are the ones who will greatly be at the disadvantage. As globalisation becomes inevitable, it is important to determine how far have the rural people been affected by the process and their responses towards the coming of the global social phenomenon. This study was conducted purposely to determine the rural East Malaysians' understanding, perception and receptiveness towards globalisation. It was also carried out to determine the impacts of the process on the social practices, political and civil rights of the rural people in East Malaysia. This study had employed multidisciplinary methods in order to collect quantitative and qualitative data from the respondents. Nonprobability sampling method such as purposive sampling was used to gather information from the respondents. This was done through a general survey based on a structured and closed-ended questionnaire. In-depth and casual interviews as well as tape-recorded conversations were also conducted for data collection. All data gathered from the study was analysed by two means: (a) content analysis based on the data derived from taped in-depth interviews, and (b) analysis of data using the standard SPSS (Social Package for Social Science). This study had managed to conduct a survey on 605 rural East Malaysians from various ethnic backgrounds in Sabah and Sarawak. This study had shown that most of the respondents were familiar with the concept of globalisation and that they understood what the process is meant. However, their understanding was limited or rather influenced by their educational attainment and exposure to the mass media. This probably indicate that they were not able to elaborate and discuss more about globalisation - such as how the process began and what it really entailed. In terms of perception towards globalisation, most of the respondents seemed to give a very positive response. They agreed that globalisation contributed massively towards Malaysia's economic and sociocultural progress. Only a small number of the respondents were against the process. Most of the respondents were also receptive towards globalisation. This was shown through their readiness in using global tools, watching global movies and listening to global songs. Apparently, they were also aware of their political and civil rights which must be given due attention by the government. In terms of social practices, globalisation had caused very minimal effects to the respondents. This was due to the fact that the process happened much slower in terms of its intensity, rapidity, multiplicity, and accessibility in the rural areas. In conclusion, this study had shown that the respondents were willing to learn and be involved in various developments implemented by the government. Moreover, in the name of progress and modernity, the rural people in East Malaysia seemed to give a very important message to convey: They wanted to be involved in globalisation and play their role as well. It is obvious that even though most of the rural people in East Malaysia are not technologically literate but they have the aspiration to develop themselves and contribute something to Malaysia's rapid modernity and progress.